Obtención de plantas in vitro del cultivo de la frambuesa (Rubus idaeus) mediante micropropagación, en el Cantón Cevallos, Provincia Tungurahua - Ugsha Chaluiza, Eveling Liseth (2022)
The research was carried out in the biotechnology laboratory "VITRO PLANTS" in Barrio San Fernando, in the Cevallos Canton, Province of Tungurahua, the raspberry (Rubus idaeus), with the main objective of obtaining in vitro plants of the raspberry crop through micropropagation. The in vitro propagation of Rubus idaeus is carried out from a plant cutting that is called nodal explant or micro stakes to guarantee the genetic quality of the new clones that can be marketed in nurseries or at the laboratory level, generating economic income for those who develop the sale of raspberries, it proceeded to prepare treatments for micropropagation culture media with Murashige and Skoog salts, with different growth regulators such as Benzylaminopurine, Kinetin, Gibberellic Acid, and a control in which no hormone added to determine which of the hormones is more effective, The different variables under study were evaluated such as shoot height (cm), number of leaves per explant, number of shoots formed per explant, number of leaves per shoot, organogenic callus formation, percentage of contamination, root length, root length per explant. A completely randomized design (CRD) was used, with four treatments and ten replications. In addition, the Tukey's multiple range test at 5% probability was used with an Infostat statistical program with the treatments T1 MS+AG3(mg/L) +BAP(1mg/L), T2 MS+KN (mg/L) +AG3(0.25ml), T3 MS + BAP (mg/L), T4 MS (mg) control. In conclusion, observed that the treatment T1 MS+AG+BAP was very effective for raspberry helping in the growth and development of the plant, achieving an effective result in all the variables evaluated in the in vitro process on the contrary, with T2 MS+AG+KN.